Do personal resources mediate the effect of perceived organizational support on emotional exhaustion and job outcomes? - Karatepe, Osman M. (Emerald Group Publishing Ltd, 2015)
Purpose - The purpose of this paper is to examine personal resources as a mediator of the effect of perceived organizational support on emotional exhaustion, extra-role customer service and turnover intentions. Design/methodology/approach - Using data collected from frontline hotel employees with a one-month time lag in Cameroon, the relationships were assessed via structural equation modeling. Positive affectivity, intrinsic motivation and self-efficacy were treated as the indicators of personal resources. Findings - The results suggest that positive affectivity, intrinsic motivation and self-efficacy are significant indicators representing personal resources. As hypothesized, personal resources fully mediate the effect of perceived organizational support on emotional exhaustion, extra-role customer service and turnover intentions. Specifically, frontline employees who receive sufficient support from the organization are high in positive affectivity, intrinsically motivated and self-efficacious at elevated levels. Such employees, in turn, experience low levels of emotional exhaustion and turnover intentions and display high levels of extra-role customer service behaviors. Originality/value - The current paper contributes to the hospitality management literature by investigating personal resources as a mediator of the impact of perceived organizational support on emotional exhaustion and the aforementioned job outcomes.
Keywords: Internal marketing; Hotel management; Human resource management; Cameroon; Emotional exhaustion; Extra-role customer service; Hotel employees; Organizational support; Personal resources; Turnover intentions